A systematic review characterizing on-farm sources of Campylobacter spp. for broiler chickens. - Agnes Agunos; Lisa Waddell; David Léger; Eduardo Taboada (PLoS ONE)
Campylobacter and antimicrobial-resistant Campylobacter are frequently isolated from broiler chickens worldwide. In Canada, campylobacteriosis is the third leading cause of enteric disease and the regional emergence of ciprofloxacin-resistant Campylobacter in broiler chickens has raised a public health concern. This study aimed to identify, critically appraise, and synthesize literature on sources of Campylobacter in broilers at the farm level using systematic review methodology. Literature searches were conducted in January 2012 and included electronic searches in four bibliographic databases. Relevant studies in French or English (n = 95) conducted worldwide in any year and all study designs were included. Risk of Bias and GRADE criteria endorsed by the Cochrane collaboration was used to assess the internal validity of the study and overall confidence in the meta-analysis. The categories for on-farm sources were: broiler breeders/vertical transfer (number of studies = 32), animals (n = 57), humans (n = 26), environment (n = 54), and water (n = 63). Only three studies examined the antimicrobial resistance profiles of Campylobacter from these on-farm sources. Subgroups of data by source and outcome were analyzed using random effect meta-analysis. The highest risk for contaminating a new flock appears to be a contaminated barn environment due to insufficient cleaning and disinfection, insufficient downtime, and the presence of an adjacent broiler flock. Effective biosecurity enhancements from physical barriers to restricting human movement on the farm are recommended for consideration to enhance local on-farm food safety programs. Improved sampling procedures and standardized laboratory testing are needed for comparability across studies. Knowledge gaps that should be addressed include farm-level drug use and antimicrobial resistance information, further evaluation of the potential for vertical transfer, and improved genotyping methods to strengthen our understanding of Campylobacter epidemiology in broilers at the farm-level. This systematic review emphasizes the importance of improved industry-level and on-farm risk management strategies to reduce pre-harvest Campylobacter in broilers.